Early‐postnatal iron deficiency impacts plasticity in the dorsal and ventral hippocampus in piglets. Issue 59 (19th March 2017) - Nelissen, Ellis; De Vry, Jochen; Antonides, Alexandra; Paes, Dean; Schepers, Melissa; van der Staay, Franz Josef; Prickaerts, Jos; Vanmierlo, Tim
Abstract: In this study, we investigated whether alterations in plasticity markers such as brain‐derived neurotrophic factor (BDNF), p75 neurotrophin receptor (p75 NTR ) and tyrosine receptor kinase B (TrkB) are underlying iron deficiency (ID)‐induced cognitive impairments in iron depleted piglets. Newborn piglets were either fed an iron‐depleted diet (21 mg Fe/kg) or an iron‐sufficient diet (88 mg Fe/kg) for four weeks. Subsequently, eight weeks after iron repletion (190–240 mg Fe/kg) we found a significant decrease in mature BDNF (14 kDa) and proBDNF (18 kDa and 24 kDa) protein levels in the ventral hippocampus, whereas we found increases in the dorsal hippocampus. The phosphorylation of cAMP response element binding protein (CREB) follows the mature BDNF protein level pattern. No effects were found on BDNF and CREB protein levels in the prefrontal cortex. The protein levels of the high affinity BDNF receptor, TrkB, was significantly decreased in both dorsal and ventral hippocampus of ID piglets, whereas it was increased in the prefrontal cortex. Together, our data suggest a disrupted hippocampal plasticity upon postnatal ID.